Maresin 1 protects the liver against ischemia/reperfusion injury via the ALXR/Akt signaling pathway - Da Tang; Guang Fu; Wenbo Li; Ping Sun; Patricia A. Loughran; Meihong Deng; Melanie J. Scott; Timothy R. Billiar (BMC, 2021)
Abstract Background Hepatic ischemia/reperfusion (I/R) injury can be a major complication following liver surgery contributing to post-operative liver dysfunction. Maresin 1 (MaR1), a pro-resolving lipid mediator, has been shown to suppress I/R injury. However, the mechanisms that account for the protective effects of MaR1 in I/R injury remain unknown. Methods WT (C57BL/6J) mice were subjected to partial hepatic warm ischemia for 60mins followed by reperfusion. Mice were treated with MaR1 (5-20 ng/mouse), Boc2 (Lipoxin A4 receptor antagonist), LY294002 (Akt inhibitor) or corresponding controls just prior to liver I/R or at the beginning of reperfusion. Blood and liver samples were collected at 6 h post-reperfusion. Serum aminotransferase, histopathologic changes, inflammatory cytokines, and oxidative stress were analyzed to evaluate liver injury. Signaling pathways were also investigated in vitro using primary mouse hepatocyte (HC) cultures to identify underlying mechanisms for MaR1 in liver I/R injury. Results MaR1 treatment significantly reduced ALT and AST levels, diminished necrotic areas, suppressed inflammatory responses, attenuated oxidative stress and decreased hepatocyte apoptosis in liver after I/R. Akt signaling was significantly increased in the MaR1-treated liver I/R group compared with controls. The protective effect of MaR1 was abrogated by pretreatment with Boc2, which together with MaR1-induced Akt activation. MaR1-mediated liver protection was reversed by inhibition of Akt. Conclusions MaR1 protects the liver against hepatic I/R injury via an ALXR/Akt signaling pathway. MaR1 may represent a novel therapeutic agent to mitigate the detrimental effects of I/R-induced liver injury.